The Impacts of Authentic Assessment on Students Skills in Classrooms: A Qualitative Study - Sayed Abas Hashami; Nisar Ahmad Arya; Rahmatullah Katawazai; Saifurrahman Rahmani; Mohammad Sharif Hasanzoy; Abdul Rahim Rahimi; Fazal Rahman Alizai (Science and Education, 2024)
This paper qualitatively studies the effectiveness of authentic assessment in classrooms that covers the years (2016 to 2019). Research articles were selected through different databases from Science Direct, Google Scholar, and Academia.edu. Findings of the study reveal that studies on authentic assessment in the different types of classrooms shows positive effects on students’ skills. It was also found that using such kind of assessment types are not only useful but recommended to language teachers to use them in different types of classrooms. The study also revealed that the dominant research design used in these studies were qualitative and quantitative in secondary and tertiary levels of different contexts. The aims of this systematic study is that can be excerpted from the relative articles as presented in table 1 are to describe the dominant kind of authentic assessment used by the teachers in different classes and to know about the effect and implementation of authentic assessment types in the higher education institutions. The review also suggests that using authentic assessment remains a potential type of assessment that can improve student’s different skills and capabilities in different contexts.